Interactive cartographic visualization for mapping residential property overhang in Klang Valley, Malaysia 2021 / Nurul Ain Nasuha Jupery, Muhammad Haqim Zulkifli and Dr Mohd Shahmy Mohd Said - Jupery, Nurul Ain Nasuha; Zulkifli, Muhammad Haqim; Mohd Said, Mohd Shahmy (College of Built Environment, 2023)
Bernama and EdgeProp news have reported that the flaw in the real estate market is due to a lack of information.